Butterfly Assemblages Associated with Invasive Tamarisk (Tamarix spp.) Sites: Comparisons with Tamarisk Control and Native Vegetation Reference Sites. (19th August 2013) - Nelson, S. Mark; Wydoski, Rick
Abstract : We studied butterfly assemblages at six types of riparian landscapes in five different watersheds in the southwestern United States (n = 34 sites). Sites included exotic-invasive Tamarix ramosissima (tamarisk) dominated sites; sites where tamarisk was controlled, but not actively revegetated; sites revegetated with upland plants; sites where control was followed with riparian plant revegetation; native riparian vegetation sites; and sites that were a mixture of native and tamarisk vegetations. Local butterfly species were linked regionally by identifying species consisting of more sensitive butterflies that are less resilient to vegetation changes and environmental perturbations and then identifying a subgroup that was reported from all watersheds. This allowed for a regional assessment relevant to all watersheds. Significant differences were found between the abundance of these in-common disturbance sensitive species at different landscapes. Sites where tamarisk was removed without restoration had butterfly metrics similar to the low values at tamarisk sites. The assumption that tamarisk removal is sufficient to recover sensitive species was not true in cases we examined. Soil moisture and riparian condition were identified as important variables associated with abundance of more sensitive butterfly species. Results support the importance of reinstating stream-flow regimes and suggest active restoration of sites if sensitive riparian wildlife species are desired.